Project-Based Science E-Module to Stimulate the Scientific Attitude of Early Children - Deta Mei Sarah; Fitri April Yanti; Melia Eka Daryati; Rendy Wikrama Wardana (Universitas Pendidikan Ganesha, 2024)
The current problem is that science learning is still centered on the teacher, so children's attention needs to be more focused because children are not taught to be directly involved in the science process. This study aims to develop a project-based science e-module to stimulate the scientific attitude of early childhood. The method used in this study is the research and development method with a 4D development model consisting of defining, designing, developing, and disseminating. The study subjects were learning media experts, learning material experts, and language experts. The subjects of the product trial were 4 IT kindergarten teachers. The data collection method was through a questionnaire. The data collection instrument was a questionnaire sheet. The techniques used to analyze the data were qualitative and quantitative descriptive analysis. The results of the study were obtained through expert validation and teacher response questionnaires, with an average result from the material expert validator of 2.94 (Quite Appropriate), an average result from the media expert validator of 3.6 (Appropriate), and an average result from the language validator of 4 (Appropriate). For the results of teacher responses to project-based science e-modules to stimulate scientific attitudes, the average percentage of assessments was 46.528% with the category